DEVELOPMENT OF THE ESSAY GENRE IN UZBEKISTAN FROM THE YEARS OF INDEPENDENCE - Aslbek Ergashev (Web of Journals Publishing, 2024)
Modern Uzbek essays, freed from ideological clichés, had the opportunity to look freely at its historical past, which was expressed in comments about the underestimation of Uzbek literary traditions of the last century. In the process of creating short but original essays, critics begin to consider our cultural heritage as a single national treasure.
Keywords: Essay, Essayistics, ideological clichés.